Faith-Based Environmental Education: The Role of Ecotheology in Developing Ecoliteracy among Muslim Boarding Students (Architecture Image Studies, 2025)
Indonesia is currently facing a serious environmental crisis driven by increasingly exploitative human behavior. Environmental education has the potential to be integrated into various forms of education, including non-formal education such as Islamic boarding schools (pondok pesantren). As educational institutions that not only teach religious knowledge but also cultivate social values and character, pesantren hold significant potential for instilling environmental awareness and care based on Islamic teachings. One concept that is highly relevant in this context is ecotheology. Ecotheology is a form of constructive theology that explains the relationship between religion and the environment. Within ecotheology, the principles of tawhid, creation (khalq), balance (mizan), and the trust of stewardship (amanah khalifah) affirm that humans are obliged to protect Allah’s creation. Ecotheology plays an important role in fostering environmental awareness and concern by promoting education, advocacy, action, and funding for ecological management. Pondok Pesantren Fadhlul Fadhlan implements the concept of an “eco-pesantren” as an effort to equip students (santri) with both religious knowledge and practical skills. The integration of ecotheological teachings and ecoliteracy through concrete environmental care practices has a positive impact on the pro-environmental behavior of students at Pondok Pesantren Fadhlul Fadhlan. Therefore, applying ecotheology within the learning process is crucial for enhancing environmental awareness and concern. This study employs a quantitative research approach with a survey method. It focuses on analyzing the level of ecotheology-based environmental perception and the level of ecoliteracy among students of Pondok Pesantren Fadhlul Fadhlan in Semarang City. The research was conducted at Pondok Pesantren Fadhlul Fadhlan, with participants consisting of 90 junior high school students and 105 senior high school students, totaling 195 participants. The data sources comprise both primary and secondary data. Data were analyzed using SmartPLS 4 with the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique and Multiple Group Analysis (MGA) Bootstrapping, aiming to maximize the R-square value and minimize residuals or prediction errors. The findings indicate that the substantive integration of ecotheology significantly enhances students’ environmental literacy. The ecotheological approach operationalizes religious principles—particularly those embodied in the indicator of tawhid—within ecological concepts, thereby enabling students to understand their responsibility to protect nature as an integral part of religious practice. The implementation of ecotheology nurtures cognitive, affective, and behavioral dimensions that are oriented toward sustainable environmental care.